China’s one-child policy amplifies intergenerational inequality via enlarged differential fertility - Yewen Yu; Yi Fan; Junjian Yi (Proceedings of the National Academy of Sciences, 2026)
Using the staggered rollout of China’s one-child policy (OCP) across provinces and birth cohorts as a quasi-natural experiment, we demonstrate that differential fertility between richer and poorer households exacerbates intergenerational income inequality. Rural/poorer families, who are less constrained by the OCP than their urban/richer counterparts, tend to have more children but invest less in each child’s human capital. This reduction in mobility is primarily driven by the rising economic status of children born to urban/wealthier families. Our estimates suggest that the OCP accounts for approximately 25% of the observed decline in intergenerational income mobility in China and thus highlight a demographic channel through which economic inequality persists across generations.